22 PROCEDURAL SEDATION FOR THE REDUCTION OF PAEDIATRIC FOREARM FRACTURES: EVOLUTION OF CARE. (10th December 2015) - Mulpuri, K.; Tennant, S.; Tritt, B.; Choit, R.; Tredwell, S.
Abstract : Purpose: The management of forearm fractures in children represents a significant part of paediatric orthopaedic practice. Recently, the manipulation of such fractures has been performed, where appropriate, under procedural sedation in the emergency room, using ketamine anaesthesia. The aim of this study was to determine the effectiveness of forearm fracture reduction under procedural sedation in children. Methods: A pilot retrospective study comparing closed forearm fractures treated at our institution in the years 1995 and 2003 were undertaken. Radiological outcome in terms of residual angulation and displacement were determined at each clinic visit. Results: In 1995, before procedural sedation was used, 145 forearm fractures were managed in the operating room, and in 2003 out of the 134 forearm fractures requiring reduction, 74 were managed with procedural sedation in the emergency department. The mean waiting time for reduction under general anaesthesia was 522 minutes (range 60-1465) while the mean waiting time for procedural sedation was 236 minutes (range 45-1030). Thirteen patients (33%) had to wait overnight for reduction under general anaesthesia and 6 patients (8.3%) waited overnight for procedural sedation. Mean true angulation was similar in both groups, 26.9 degrees (range 6-70) for the procedural sedation group and 27.5 degrees (range 8.5-63) for the general anaesthesia group. Conclusions: There was no difference in clinical or radiological outcome between those fractures reduced under procedural sedation and those reduced under general anaesthesia in the operating room. Procedural sedation proved to be an effective method of managing paediatric forearm fractures requiring reduction.